Exploring How Motivation and the Work Environment Drive Employee Performance: An In-depth Study of a Retail Company in Bandung - Rendi Rezaldi; Retno Resawati; Asep Rochyadi Suherman (JURNAL COMPUTECH & BISNIS, 2026)
Research Problem: The study addresses how work motivation and work environment affect employee performance, emphasizing the crucial ways these elements shape workplace behaviors and outcomes. Research Objective: The primary aim of this research is to explore the relationships between work motivation, work environment, and employee performance specifically within the retail sector in Bandung. By focusing on this particular context, the study seeks to understand how motivational factors and the surrounding work environment influence the performance levels of employees in retail establishments. Method and Analysis Technique: A mixed-method approach combining surveys, interviews, and quantitative data analysis was employed to gather and analyze data. Statistical analyses such as path analysis were used to explore the relationships between the variables. Research Findings: The research findings indicate that a supportive work environment significantly contribute to employee performance. Moreover, motivation, individual behavior, and voluntary pro-environmental actions were influenced by these factors. Originality of the Study: The findings from this study will help illuminate how local cultural, economic, and market conditions influence employee motivation and performance within retail settings, shedding light on the unique interplay between work motivation, work environment and employee performance in this setting. The study adds to the originality of research in understanding how these factors interact and impact workplace behaviors and outcomes in a retail industry context.